Artificial intelligence and labour relations - Toyama Miyagusuku, Jorge (2024)
Artificial intelligence is impacting labour relations through job reduction, the creation of new positions, and the use of algorithms in labour decisions, among other ways. Its impact is evident in the application of artificial intelligence in personnel selection, the employment relationship itself, and its termination. This article will analyse the labour conflicts arising from the implementation of artificial intelligence, highlighting both the points of convergence and disagreement between artificial intelligence and labour law.Likewise, in the absence of specific legal regulations, possible solutions are proposed, such as employing the proportionality test as a tool for resolving labour disputes related to artificial intelligence. It is crucial to balance business efficiency with the protection of workers’ fundamental rights. Finally, the article emphasizes that labour conflicts should be prevented through social dialogue and policies that ensure transparency in the use and effects of artificial intelligence.